2023
DOI: 10.1037/pspa0000348
|View full text |Cite
|
Sign up to set email alerts
|

Field-specific ability beliefs as an explanation for gender differences in academics’ career trajectories: Evidence from public profiles on ORCID.Org.

Abstract: Academic fields exhibit substantial levels of gender segregation. Here, we investigated differences in field-specific ability beliefs (FABs) as an explanation for this phenomenon. FABs may contribute to gender segregation to the extent that they portray success as depending on “brilliance” (i.e., exceptional intellectual ability), which is a trait culturally associated with men more than women. Although prior work has documented a relation between academic fields’ FABs and their gender composition, it is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…Notably, even 5-to 7-year-old children were less likely to select a girl than a boy teammate when a game was described as being "for really, really smart" children, suggesting that informal gatekeeping processes start early in life (e.g., in children's peer groups). Evidence that connects these gender biases with women's underrepresentation in brilliance-oriented fields and occupations was reported by Leslie and colleagues (2015): The more a field valued brilliance, the more its members endorsed biased beliefs such as that men are "more suited" than women to do "high-level work" in their field, and endorsement of such gender-biased beliefs accounted for approximately 70% of the association between a field's FABs and the gender composition of its PhDs (see also Hannak et al, 2023).…”
Section: Mechanisms: How Do Field-specific Ability Beliefs Act As An ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Notably, even 5-to 7-year-old children were less likely to select a girl than a boy teammate when a game was described as being "for really, really smart" children, suggesting that informal gatekeeping processes start early in life (e.g., in children's peer groups). Evidence that connects these gender biases with women's underrepresentation in brilliance-oriented fields and occupations was reported by Leslie and colleagues (2015): The more a field valued brilliance, the more its members endorsed biased beliefs such as that men are "more suited" than women to do "high-level work" in their field, and endorsement of such gender-biased beliefs accounted for approximately 70% of the association between a field's FABs and the gender composition of its PhDs (see also Hannak et al, 2023).…”
Section: Mechanisms: How Do Field-specific Ability Beliefs Act As An ...mentioning
confidence: 92%
“…Academics' FABs predicted the percentage of women in their fields: The more strongly a field's members emphasized the role of brilliance in achieving success, the lower was women's representation at the doctoral level (Fig. 2A; see also Hannak et al, 2023;Meyer et al, 2015;Storage et al, 2016). The degree to which a field emphasized brilliance was also inversely correlated with the percentage of doctoral degrees awarded to Black Americans, who-like women-are targeted by negative stereotypes about their intellectual abilities (Fig.…”
mentioning
confidence: 95%
“…Our investigation of the structural barriers to girls’ and women’s participation in chess has implications that extend beyond this specific domain. For instance, the present work informs theory about FABs as an explanation for occupational gender segregation (e.g., Muradoglu et al, 2023) by testing the generality of the FAB model in explaining gender segregation beyond educational or academic pursuits (e.g., Hannak et al, 2023; Leslie et al, 2015; Muradoglu et al, 2022) and at the individual rather than group level: Although research inspired by the FAB account has documented a link between brilliance-oriented FABs and prejudice against women at the group level (e.g., more brilliance-oriented fields also show stronger biases against women; Hannak et al, 2023; Leslie et al, 2015; Meyer et al, 2015), no research to date has examined whether this link is also observed at the individual level. Finally, no evidence thus far speaks to whether brilliance-related beliefs relate to parents’ and mentors’ attitudes toward their own children and mentees, respectively.…”
Section: Why Are There So Few Girls and Women In Chess?mentioning
confidence: 80%
“…From a theoretical standpoint, the present findings contribute to theories of gender segregation. They are particularly relevant to the FAB account of this phenomenon, according to which contexts in which brilliance is prized are less conducive to women’s participation, due in part to the prejudice that women encounter in these contexts (e.g., Bian et al, 2018; Hannak et al, 2023). First, it is noteworthy that no prior work tested the predictions of the FAB account in a leisure domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation